(untitled) (Nepalese Journal of Radiology, 2025)
Superior mesenteric artery (SMA) syndrome is a rare vascular compression disorder resulting from compression of 3rd part of the duodenum between the aorta and SMA due to loss of intervening mesenteric fat pad. Management is usually conservative but failure of which warrants surgical intervention. Imaging modalities document and characterize the typical findings, and are considered paramount in the diagnosis and management of this disease. Here, we present a case of SMA syndrome in an 18-year-old adult presenting with nausea, vomiting, and abdominal pain. Contrast-enhanced study (CECT) of the abdomen and pelvis showed typical findings of SMA syndrome. The patient underwent surgery (duodenojejunostomy) with uncomplicated postoperative recovery.